2022
DOI: 10.36922/ijps.v7i2.392
|View full text |Cite
|
Sign up to set email alerts
|

Residential inequalities in child mortality in Ethiopia: Multilevel and decomposition analyses

Abstract: Ethiopia is among the five countries which account for half of the global under-five deaths, with the under-five mortality rate of 67 deaths/1000 live births in 2016. Ethiopia had significant inequalities in child mortality between rural and urban areas where the risk of child mortality is largely higher in rural than urban areas. Inequalities in the distribution of factors influencing child mortality need to explain the gap between and within urban-rural areas. The study used the risk of child mortality as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The present study revealed a higher likelihood of healthcare-seeking delay among caregivers residing in rural areas compared to those in urban settings, which aligns with findings from previous studies conducted in Nekemte town ( 34 ), Bahir Dar city ( 35 ), Hawassa ( 49 ), Kaduna Nigeria ( 50 ), and India ( 51 ). This might be due to variations in the accessibility of public health services, resulting from geographical distance and media exposure ( 52 ). Moreover, it could also be due to challenges posed by poverty and limited healthcare access in rural areas ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study revealed a higher likelihood of healthcare-seeking delay among caregivers residing in rural areas compared to those in urban settings, which aligns with findings from previous studies conducted in Nekemte town ( 34 ), Bahir Dar city ( 35 ), Hawassa ( 49 ), Kaduna Nigeria ( 50 ), and India ( 51 ). This might be due to variations in the accessibility of public health services, resulting from geographical distance and media exposure ( 52 ). Moreover, it could also be due to challenges posed by poverty and limited healthcare access in rural areas ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…These factors can lead to waterborne diseases and other complications that can result in child mortality [15]. In sub-Saharan African countries, rural residents had an 11% greater probability of under-five mortality than did urban residents between 2010 and 2018 [16]. In Ethiopia, rural residency is also a significant factor that can contribute to a higher under-five mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…Inequalities in social groups also contributed greatly to under-five mortality in Ethiopia. In general, rural areas have a greater risk of child mortality than do urban areas [16,17].…”
Section: Introductionmentioning
confidence: 99%